2000
DOI: 10.1002/1521-3765(20001117)6:22<4082::aid-chem4082>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tin and Tin Oxide Nanoparticles of Low Size Dispersity for Application in Gas Sensing

Abstract: Nanocomposite core-shell particles that consist of a Sn0 core surrounded by a thin layer of tin oxides have been prepared by thermolysis of [(Sn(NMe2)2)2] in anisole that contains small, controlled amounts of water. The particles were characterized by means of electronic microscopies (TEM, HRTEM, SEM), X-ray diffraction (XRD) studies, photoelectron spectroscopy (XPS), and Mossbauer spectroscopy. The TEM micrographs show spherical nanoparticles, the size and size distribution of which depends on the initial exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
98
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 60 publications
11
98
0
Order By: Relevance
“…X-ray structural analyses confirmed that Mn 3 O 4 nanoparticles are found to be slightly temperature dependent at higher frequency. These results indicate that the dielectric properties showed a usual dielectric dispersion explained on the basis of the Maxwell-Wagner model.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…X-ray structural analyses confirmed that Mn 3 O 4 nanoparticles are found to be slightly temperature dependent at higher frequency. These results indicate that the dielectric properties showed a usual dielectric dispersion explained on the basis of the Maxwell-Wagner model.…”
Section: Resultsmentioning
confidence: 80%
“…Metal oxide nanocrystals are widely applied in catalysis, energy storage, magnetic data storage, sensors, and ferrofluids [1][2][3][4]. Tetramanganese oxides (Mn 3 O 4 ) are particularly used as main sources of ferrite materials [5] and applied in numerous industrial fields such as magnetic [6], electrochemical [7], and catalysis [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…These defects bring on additional electronic states in the band gap, which can mix with the intrinsic states to a substantial extent and which may influence the spacing of the energy levels and the optical properties of nanopowders. A variety of methods were used to prepare SnO 2 nanostructures, such as hydrothermal method, polymeric and organometallic precursor synthesis, soncation procedure, microwave synthesis and surfactant-mediated method [8][9][10][11][12][13][14][15][16][17][18] . Zinc is a quite active element.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33] We have shown that this methodology can be extended to the synthesis of nanoparticles of metal oxides with a precise control of morphology. [34][35][36][37] which can be, in a second step, oxidized into well crystallized nanoparticles of the corresponding oxides, without coalescence. We recently reported a direct organometallic route to prepare ZnO colloidal solutions containing nanoparticles of controlled size and shape.…”
Section: Introductionmentioning
confidence: 99%